PEMBERDAYAAN KOMITE SEKOLAH DAN GURU DALAM RANGKA DIVERSI PADA PIDANA ANAK DI SMAN 5 SURAKARTA - Fatma Ayu Jati Putri; Supriyono Supriyono (Bajang Institute, 2023)
Both from the family and non-family environment can have an impact on children's criminal behavior. Parental attitudes, level of family cohesion, and physical violence are important factors in shaping criminal orientation and behavior during adolescence. Therefore, the involvement of parents, education boards and school committees in the teaching and learning process has a significant influence in efforts to prevent juvenile delinquency.The aim of this study is to gain a deeper understanding of the role of the School Committee and Teachers in diversion efforts in juvenile crime at SMAN 51 East Jakarta. School committee-based empowerment is used to understand social phenomena from the perspective of the individuals or groups involved. Data was collected through interviews with School Committee members,teachers,parents and students to explore their views, attitudes and experiences regarding diversion in juvenile crime. Data analysis was carried out using a thematic analysis approach. The results show the important role of School Committees and Teachers in preventing juvenile delinquency. Various family and non-family factors influence child crime, so empowering the School Committee becomes relevant in diversion strategies. The role of School Committees and Teachers is crucial in efforts to prevent and divert juvenile crime. Committee empowerment and diversion strategies must continue to be improved so that children in conflict with the law can continue their education with a better future